PENINGKATAN KEMAMPUAN MENULIS TEKS DESKRIPSI MELALUI METODE PICTURE AND PICTURE BERBANTUAN DISPLAY BOARD PADA SISWA KELAS VII SMP NEGERI 7 MADIUN TAHUN AJARAN 2026/2027 - Mutiara Arifa, Rahmadona; Kuncoro Hadi, Panji; Budiharto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing is the ability to express thoughts, opinions, and feelings in writing to others. Clarity of ideas must be supported by the use of correct language, vocabulary, grammar, and spelling. However, the reality in the field shows that the ability to write descriptive texts in Indonesian language subjects is still very low. From this problem, the purpose of this study is to determine the improvement of the ability to write descriptive texts with the picture and picture method assisted by a display board. This study is a type of classroom action research carried out in 2 research cycles. Each research cycle consists of 4 phases, namely planning, implementation, observation, reflection. The subjects involved in this study were class VII F of SMP Negeri 7 Madiun which consisted of 26 students. Data collection in this study was carried out by qualitative and quantitative analysis. The results obtained in this study indicate that student learning outcomes in writing competencies in the learning process of cycle I were 65.38%, in cycle II student learning outcomes in writing competencies were 92.31%. It can be concluded that the application of the picture and picture method assisted by a display board can improve the ability to write descriptive texts of class VII F students of SMP Negeri 7 Madiun.